2020
DOI: 10.1037/fsh0000493
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety interventions delivered in primary care behavioral health routine clinical practice.

Abstract: Introduction: Although anxiety is highly prevalent in primary care and a top reason for referral to primary care behavioral health (PCBH) services, there are limited data on which anxiety interventions are used in routine PCBH practice. The objective of this study was to identify interventions delivered when treating anxiety in PCBH practice. Method: We conducted an online survey of PCBH providers regarding their clinical practice with patients who present for treatment of anxiety symptoms. The final sample co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…They emphasized the need for flexibility to tailor treatment to individual patients’ needs and preferences, as not all modules would be relevant to everyone. BHPs reported high familiarity and comfort with skills in MAST-V except for exposure and mindfulness meditation, consistent with prior research on PCBH usual care (Shepardson, Minnick, & Funderburk, 2020). We thus added a background section to review the goals and rationale for all modules, which clarifies the scope to reduce confusion or misperceptions.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…They emphasized the need for flexibility to tailor treatment to individual patients’ needs and preferences, as not all modules would be relevant to everyone. BHPs reported high familiarity and comfort with skills in MAST-V except for exposure and mindfulness meditation, consistent with prior research on PCBH usual care (Shepardson, Minnick, & Funderburk, 2020). We thus added a background section to review the goals and rationale for all modules, which clarifies the scope to reduce confusion or misperceptions.…”
Section: Discussionsupporting
confidence: 82%
“…With little to no guidance for brief behavioral anxiety treatment in PCBH, BHPs are left to idiosyncratically adapt specialty care protocols, frequently drawing from cognitive-behavioral therapy (CBT; Funderburk et al, 2011). BHPs reported using an average of 5.8 interventions for anxiety within a single PCBH appointment, with psychoeducation (95%), relaxation training (64%), and supportive therapy (61%) being most common, while cognitive restructuring (45%) and exposure (21%) were used less often (Shepardson, Minnick, & Funderburk, 2020). These findings raise questions about the appropriateness and potency of intervention that patients are receiving.…”
Section: Intervention Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, exposure therapy (ET), arguably the most effective intervention for anxiety (Deacon & Abramowitz, 2004; Foa & McLean, 2016; Olatunji, Cisler, & Deacon, 2010), has received little attention in the PC-based anxiety treatment literature. Indeed, a survey of PCBH providers regarding intervention techniques used in the most recent visit with a patient referred for anxiety found that only 21% delivered ET (Shepardson, Minnick, & Funderburk, 2020). Furthermore, research in the context of evidenced based treatment for anxiety in primary care specifically highlights the importance of decreasing avoidance as such behavior may persist beyond symptom improvement and necessitate a behavioral approach (Roy-Byrne et al, 2009).…”
mentioning
confidence: 99%